2013
DOI: 10.5194/we-13-31-2013
|View full text |Cite
|
Sign up to set email alerts
|

Diversity did not influence soil water use of tree clusters in a temperate mixed forest

Abstract: Abstract. Compared to monocultures, diverse ecosystems are often expected to show more comprehensive resource use. However, with respect to diversity-soil-water-use relationships in forests, very little information is available. We analysed soil water uptake in 100 tree clusters differing in tree species diversity and species composition in the Hainich forest in central Germany. The clusters contained all possible combinations of five broadleaved tree species in one-, two-and three-species clusters (three dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Little experimental information is available on the relationship between tree mixture and water use in temperate forests (Grossiord et al, 2013), but our analysis aligns with recent results for a mixed European forest undergoing desiccation (Meißner et al, 2013) to contradict a common paradigm that more diverse ecosystems use available resources more comprehensively (e.g. Hector et al, 1999).…”
Section: Researchsupporting
confidence: 84%
See 1 more Smart Citation
“…Little experimental information is available on the relationship between tree mixture and water use in temperate forests (Grossiord et al, 2013), but our analysis aligns with recent results for a mixed European forest undergoing desiccation (Meißner et al, 2013) to contradict a common paradigm that more diverse ecosystems use available resources more comprehensively (e.g. Hector et al, 1999).…”
Section: Researchsupporting
confidence: 84%
“…We further note that the suggested complementarity in resource exploitation by beech and oak did not significantly enhance relative daily water use of the mixed over the two monocultures (combined data) under dry or rewetted conditions (Welch's t ‐tests on data for each day of the experiment, with Holm–Bonferroni correction, P > 0.05). Little experimental information is available on the relationship between tree mixture and water use in temperate forests (Grossiord et al ., ), but our analysis aligns with recent results for a mixed European forest undergoing desiccation (Meißner et al ., ) to contradict a common paradigm that more diverse ecosystems use available resources more comprehensively (e.g. Hector et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…This species‐specific plasticity might be key for their survival and competitiveness under increasing water scarcity (Volkmann et al, 2016). The spatial and temporal water source partitioning between different species is still poorly tested and contrasting results have been found (Allen et al, 2019; Bello et al, 2019; Grossiord et al, 2014; Meißner et al, 2013; Volkmann et al, 2016). While Meinzer et al (2001) highlighted the potential of niche complementarity as a competition avoidance strategy, Grossiord (2019) and Gillerot et al (2020) suggested that tree diversity does not systematically increase the performance of forest communities.…”
Section: Introductionmentioning
confidence: 99%
“…The latter observations are mirrored by patterns of soil water extraction conducted during the same period with a soil water balance modeling approach (Krämer and Hölscher ). Also in the Hainich forest, Meißner et al () found no systematic differences in water consumption among small‐sized tree clusters that differed in species composition and species richness (1–3 species). Different deuterium signatures in the xylem water of coexisting tree species in mixed stands pointed, however, at partitioning of soil water among species during a soil desiccation period and thus may indicate a certain complementarity in water use (Meißner et al ).…”
mentioning
confidence: 99%